Dynamics of Agrarian Conflict and Its Impact on Natural Resource Governance in Indonesia - Asruddin; Ronal Regen; Herlin; Armawansya; Supiardi (Pustaka Digital Indonesia, 2026)
Agrarian conflicts remain one of the most pressing challenges in the governance of natural resources in Indonesia. These conflicts frequently emerge from overlapping land ownership claims, inconsistencies in land administration systems, unequal access to and control over natural resources, conflicting sectoral regulations, and weak legal certainty in the recognition and protection of land rights. Such conditions have contributed to prolonged disputes involving local communities, indigenous peoples, private corporations, and government institutions, thereby creating significant obstacles to sustainable development and equitable resource management. This study aims to analyze the dynamics of agrarian conflicts and examine their implications for natural resource governance in Indonesia. The research employs a normative juridical approach by analyzing statutory regulations, legal doctrines, judicial principles, and relevant academic literature concerning agrarian law and natural resource governance. The findings reveal that agrarian conflicts have far-reaching consequences, extending beyond legal disputes to influence social, economic, and environmental dimensions. These conflicts contribute to social instability, reduce public trust in government institutions, hinder investment and development initiatives, and accelerate environmental degradation through unsustainable land use practices. Furthermore, unresolved conflicts weaken the effectiveness of natural resource governance by limiting policy implementation, reducing institutional coordination, and increasing the potential for recurring disputes. The study concludes that addressing agrarian conflicts requires comprehensive legal and institutional reforms. Strengthening regulatory frameworks, harmonizing sectoral policies, improving legal certainty, establishing fair and transparent conflict resolution mechanisms, and enhancing meaningful public participation are essential strategies for promoting sustainable, inclusive, and equitable natural resource governance. These measures are expected to support the realization of legal justice, environmental sustainability, and balanced socio-economic development in Indonesia while minimizing the recurrence of agrarian disputes in the future.